Morphological Description and Ethnobotanical Review of the Orphan Crop Myin-Hkwa (Centella asiatica L.) From Myanmar - Shukurova, Musavvara Khaitovna; Myint, Daisy; Yi, San San; Saw, Ohm Mar; Watanabe, Kazuo N. (Frontiers in Sustainable Food Systems, 2021)
Centella asiatica is a medicinal herb commonly known as Asiatic pennywort or gotu kola. The species is valued for its medicinal and nutritional properties. It is a perennial plant with leaves and stems that can be consumed as a green leafy vegetable. It is used as a folk remedy to cure various mild and chronic diseases due to its anti-rheumatic, antipyretic, antibacterial, antiviral, and anti-inflammatory effects, and as a mental rejuvenator. Although the species is widely distributed throughout the tropics and subtropics, its recognition was limited. The morphological description of C. asiatica is not well-documented in Myanmar, in Burmese or other local languages. Plant assessment via morphological markers is one of the ultimate methods for the primary description and characterization of their phenotypic traits. The objectives of this study were focused on the description of Myanmarese C. asiatica grown in Japan through morphological markers and a brief overview of its ethnobotanical use in Asia. Morphological characterization revealed the quantitative and qualitative differences regarding several traits among assessed C. asiatica samples. Furthermore, the study can provide information on the primary C. asiatica cultivation system in Japan, as it can be a potentially new and economically important crop for the Japanese market.